Contact sensitization to plants of the Compositae family: Data of the Information Network of Departments of Dermatology (IVDK) from 2007 to 2016. (13th December 2018) - Bauer, Andrea; Geier, Johannes; Schreiber, Sophie; Schubert, Steffen; ,
Abstract : Background: The Compositae plant family includes many thousands of species, making it one of the most widespread group of plants worldwide. Sensitization to Compositae allergens may occur in private or in occupational settings. Objectives: To monitor the current spectrum of sensitization to Compositae allergens, especially in cooks and florists. Methods: We retrospectively analysed patch test results obtained with two Compositae mixes (CMs) (CM I and CM II; switch in October 2011), their individual components, and sesquiterpene lactone (SL) mix in 1492 cooks, 851 florists, and a control group (118 358 other patients) registered in the IVDK, 2007 to 2016. Results: Florists reacted significantly more frequently to CM I and II (CM I, 8.7%; CM II, 10.6%) than did cooks (CM I, 2.1%; CM II, 0.8%) and controls (CM I, 1.3%; CM II, 1.2%). Additional testing with SL mix detected 14.3% more sensitizations than CM I or CM II alone. Conclusions: Florists are at considerable risk of sensitization to Compositae allergens. Patch testing with both CM and SL mix is recommended.